Alcohol Use, Discrimination, and Psychological Partner Abuse Among LGBQ+ College Students: Results From a Daily Diary Study - Brem, Meagan J. (Journal of interpersonal violence, 2024)
Alcohol use correlates with psychological partner abuse (PA) perpetration among lesbian, gay, bisexual, queer, and other nonheterosexual (LGBQ+) young adults. However, less is known about the proximal association between alcohol use and psychological PA within this population, which would provide valuable information for intervention development. Informed by minority stress and alcohol-related PA theories, we evaluated whether (a) psychological PA perpetration odds increased as the number of drinks consumed prior to psychological PA on a given day increased, (b) psychological PA perpetration odds were greater following heavy episodic drinking (HED) relative to non-HED, and (c) experiencing LGBQ+-specific discrimination (i.e., heterosexist harassment, incivility, and hostility) strengthened the association between daily alcohol use (number of drinks, HED) and subsequent psychological PA perpetration. LGBQ+ college students (N = 41; 75.6% women, 22.0% men, and 2.4% transgender/non-binary) completed a baseline survey of past-year discrimination before completing daily reports of their alcohol use and psychological PA for 60 consecutive days. Multilevel modeling revealed that drinking more than one usually does on a given day is positively associated with subsequent psychological PA odds (OR = 1.31, p < .001). Psychological PA was more likely following HED relative to non-HED (OR = 3.23, p < .001). Unexpectedly, experiencing discrimination was negatively associated with psychological PA odds across models (OR = .26 p = .01). No alcohol × discrimination interactions emerged. Results support alcohol use as a proximal risk factor for psychological PA among LGBQ+ college students and underscore the need for more nuanced examination of discrimination and other contextual variables in alcohol-related PA.